2015
DOI: 10.1186/s12864-015-1869-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic changes of Legionella pneumophila in water

Abstract: BackgroundLegionella pneumophila (Lp) is a water-borne opportunistic pathogen. In water, Lp can survive for an extended period of time until it encounters a permissive host. Therefore, identifying genes that are required for survival in water may help develop strategies to prevent Legionella outbreaks.ResultsWe compared the global transcriptomic response of Lp grown in a rich medium to that of Lp exposed to an artificial freshwater medium (Fraquil) for 2, 6 and 24 hours. We uncovered successive changes in gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(90 citation statements)
references
References 103 publications
7
83
0
Order By: Relevance
“…Similar results were found for bdhA and lasM, which are required for survival in water only when the temperature is above 25°C (Li and Faucher 2016;Li et al 2015). Since ∆lpg2524 did not show a defect in water during short-term exposure at 55°C when compared to the WT (data not shown), it is unlikely that the defects we observed at 37°C and 42°C were due to a lower tolerance to high temperature.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Similar results were found for bdhA and lasM, which are required for survival in water only when the temperature is above 25°C (Li and Faucher 2016;Li et al 2015). Since ∆lpg2524 did not show a defect in water during short-term exposure at 55°C when compared to the WT (data not shown), it is unlikely that the defects we observed at 37°C and 42°C were due to a lower tolerance to high temperature.…”
Section: Discussionsupporting
confidence: 82%
“…CFU of each sample was monitored once per three weeks, once per two weeks and once per week, respectively. For the samples incubated at 42°C, Live/Dead staining and flow cytometry were used to determine the membrane integrity of Lp after 7 weeks as described previously (Li et al 2015). Freshly grown KS79 was used as the control for viable cells and KS79 boiled in a water bath for 10 minutes was used as the control for dead cells.…”
Section: Survival Assays In Watermentioning
confidence: 99%
See 2 more Smart Citations
“…S9). Among the 64 genes, some have been shown to play a role in intracellular infection such as the genes from the cytochrome c maturation (ccm) locus (Viswanathan et al 2002;Naylor and Cianciotto 2004), PilR (an important regulator for pilin and flagella synthesis), the phagosomal transporter family Pht (Sauer et al 2005), or the enhanced entry protein EnhA that was shown to be important for entry in phagocytic cells (Cirillo et al 2000) and during persistence in water environments (Li et al 2015).…”
Section: The Major Disease-associated Clones Emerged Very Recentlymentioning
confidence: 99%